Connecting smallholder root and tuber growers to markets through Farmer Business Schools - International Potato Center (International Potato Center, 2019)
This book features a collection of stories of 24 women and men who participated in Farmer Business Schools in the Philippines and India, and of project staff of partner organizations who have facilitated the process. Since innovations are inherently linked to change in practices and lives, the stories were collected using the ‘most significant change’ (MSC) approach as a technique for capturing project outcomes. MSC is a qualitative evaluation tool based on community members’ response to a simple question: What do you think was the most significant change in your life brought about by this initiative? This encourages community members to tell the story of how their lives are now different and what part of that difference they value the most.